Essentials of Economics - John Sloman; Dean Garratt (United Kingdom Pearson, 2019)
This book distills introductory economics into a fraction of the space normally used by traditional economic textbooks, yet it covers all the basics most readers will need. Topics covered include: markets; supply and demand; wages; market failures and government policy; aggregate demand and supply; macroeconomic issues; national income; fiscal and monetary policy; unemployment; inflation; international trade; balance of payments, and more.
Keywords: Economics; (MGT-104) Fundamentals of Financial Decision-Making